Categorization of the surrounding world in the Tuvan, Buryat and Yakut epics through the prism of the achromatic pair white / black - Prosyannikova, Olga I.; Skorik, Ksenia V. (The New Research of Tuva, 2024)
The article examines the lexical meanings of words that help to describe the surrounding world in epic works by related ethnic groups — Tuvans, Buryats, and Yakuts. Color designations convey a person’s perception of the world and allow us to trace the process of categorizing the surrounding color space. A comparative analysis of the use of achromatic colors in the Tuvan, Buryat, and Yakut epics has revealed typological and genetic features of the worldviews of these peoples due to cultural interactions over centuries. There is a similarity in the positive perception of white and negative perception of black, as well as the actualization of connotative values and enhancement of quality through epithets. The results of the contextual analysis have shown the ability to understand the figurative meanings of adjective-color combinations, indicating the symbolic significance of flowers and their ritual significance for these ethnic groups. These characteristic features can be explained by the historical proximity, spiritual connection, and belonging to the same language group of these peoples. However, there are also differences that reflect the ethnocultural specifics of the categorization of color perceptions.